STATISTICAL ESTIMATION THE AGE INEQUALITY BY INCOME - V. Shyshkin (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The inequality of age of Ukrainian population by income is analyzed. Difference in incomes in absolute and relative terms defined. The influence of age and other factors on the inequality of age population' is estimated.